PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN BERPAKU (GEOBOARD) KONTEKSTUAL DALAM MENGENAL BANGUN DATAR KELAS IV SEKOLAH DASAR - Ulfah, Mariah; Hakim, Zerri Rahman; Setiawan, Sigit (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to examine the development process, feasibility, and students’ responses toward the use of the Geoboard learning media in fourth-grade mathematics instruction. The research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The instruments used included interview sheets, observation sheets, expert validation questionnaires, and student response questionnaires. The results of the Geoboard media development showed that the average validation score from instrument experts was 92.00% (very feasible), from media experts was 91.02% (very feasible), and from material experts was 88.03% (very feasible). Furthermore, the student response questionnaire achieved an average percentage of 95.08%, categorized as very good. Based on these findings, it can be concluded that the Geoboard learning media developed for fourth-grade mathematics lessons has been successfully created, is feasible for use in the learning process, and received very positive responses from students. The Geoboard proved to be an effective learning tool, particularly in teaching the topic of plane geometry in elementary school mathematics.